2006
DOI: 10.2214/ajr.05.0460
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Sclerosing Hemangioma Presenting as Solitary Pulmonary Nodule: Dynamic CT Findings and Histopathologic Comparisons

Abstract: On dynamic CT, sclerosing hemangioma has strong and rapid enhancement attributed histopathologically to the presence of hemangiomatous or papillary components in the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 16 publications
1
43
0
Order By: Relevance
“…The alternative designation is sclerosing pneumocytoma since current evidence suggests that sclerosing hemangiomas originate from primitive undifferentiated respiratory epithelial cells (8, 9). Dynamic enhancement characteristics of the tumors depend on the levels of histologic components (papillary, sclerotic, solid, and hemangiomatous); a hemangiomatous or papillary component reveals early and strong enhancement, while a solid or sclerotic component shows slow and persistent enhancement (10). Although these enhancement patterns of sclerosing hemangioma can sometimes look quite similar to that of capillary hemangioma, the former usually do not show a striking peripheral nodular enhancement of the latter on the early arterial phase.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative designation is sclerosing pneumocytoma since current evidence suggests that sclerosing hemangiomas originate from primitive undifferentiated respiratory epithelial cells (8, 9). Dynamic enhancement characteristics of the tumors depend on the levels of histologic components (papillary, sclerotic, solid, and hemangiomatous); a hemangiomatous or papillary component reveals early and strong enhancement, while a solid or sclerotic component shows slow and persistent enhancement (10). Although these enhancement patterns of sclerosing hemangioma can sometimes look quite similar to that of capillary hemangioma, the former usually do not show a striking peripheral nodular enhancement of the latter on the early arterial phase.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although there was no marked difference between the tumor size, density, shape and margin of the PSHs and pulmonary hamartomas, the study showed significantly higher FDG accumulation in the PSHs than in the pulmonary hamartomas. Chung et al (23) suggested that the presence of a hemangiomatous or papillary component in the tumor may lead to increased FDG uptake. Lee et al (21) attempted to analyze the mechanism or histological influencing factors of the increased FDG uptake of PSH.…”
Section: Discussionmentioning
confidence: 99%
“…CXR characteristics are sharply marked, well defined, solitary, peripheral, homogenous mass without any lobar predilection. [5] On CECT, there is contrast-enhancement of the mass with little or no peripheral calcification. There is absence of infiltration of surrounding tissues along with absence of cavities.…”
Section: Discussionmentioning
confidence: 99%